2016
DOI: 10.1016/j.adolescence.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Sexy online self‐presentation on social network sites and the willingness to engage in sexting: A comparison of gender and age

Abstract: The present study investigated whether engaging in sexy self-presentations on social network sites (SNSs) or exposure to sexy self-presentations on SNSs predicts the willingness to engage in sexting. A second aim of the present study was to investigate whether adolescent girls demonstrate stronger relationships between (exposure to) sexy online self-presentations on SNSs and willingness to sext than adolescent boys and young adult men and women. A two-wave panel survey among 953 Dutch adolescents (13-17 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 71 publications
2
43
0
2
Order By: Relevance
“…At the same time, self-report measures have been successfully used in many previous studies on antecedents and consequences of adolescents' social media use (e.g., Barker, 2009;de Vries et al, 2016;Gross, 2004), including sexy self-presentation (e.g., Baumgartner et al, 2015). Moreover, the self-report measures of (exposure to) sexy self-presentations used in the present study have shown good construct validity, as they have been associated with other types of sexual media use (e.g., reality TV, Vandenbosch et al, 2015) and sexual attitudes (e.g., instrumental attitudes toward sex and notions of women as sex objects, van Oosten et al, 2015a) in previous studies using the same data-set and in a recent study using a different sample (van Oosten & Vandenbosch, 2017). Similarly, our self-report measure of hypergender orientation is based on validated self-report scales for hyperfemininity and hypermasculinity among adults (Mosher & Sirkin, 1984;Murnen & Byrne, 1991).…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 86%
See 2 more Smart Citations
“…At the same time, self-report measures have been successfully used in many previous studies on antecedents and consequences of adolescents' social media use (e.g., Barker, 2009;de Vries et al, 2016;Gross, 2004), including sexy self-presentation (e.g., Baumgartner et al, 2015). Moreover, the self-report measures of (exposure to) sexy self-presentations used in the present study have shown good construct validity, as they have been associated with other types of sexual media use (e.g., reality TV, Vandenbosch et al, 2015) and sexual attitudes (e.g., instrumental attitudes toward sex and notions of women as sex objects, van Oosten et al, 2015a) in previous studies using the same data-set and in a recent study using a different sample (van Oosten & Vandenbosch, 2017). Similarly, our self-report measure of hypergender orientation is based on validated self-report scales for hyperfemininity and hypermasculinity among adults (Mosher & Sirkin, 1984;Murnen & Byrne, 1991).…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 86%
“…Thus, the more adolescents, female or male, endorse a hypergender orientation, the more likely they are to engage in sexy self-presentation or to look at others' sexy selfpresentation. It should be noted that a recent study did not find a difference between adolescent boys and girls in their engagement in sexy self-presentation, and found that boys exposed themselves to the sexy self-presentations of others more than girls (van Oosten & Vandenbosch, 2017). Previous research thus suggests that the role of gender, in the sense of biological sex, in research on the frequency, predictors, and consequences of young people's (self-) sexualization is lacking or inconsistent.…”
Section: Hypergender Orientation Predicts Sexy Self-presentation and mentioning
confidence: 87%
See 1 more Smart Citation
“…The willingness to engage in NCFS is a much more subtle measure which is often used for sexual risk behavior and can thus be expected to be more suitable for measuring antisocial behaviors such as NCFS. Moreover, a focus on behavioral willingness fits in a body of research on risk behavior based on the prototype-willingness model (e.g., Gerrard et al, 2008), and the role of media herein (e.g., Boot, Peter, & van Oosten, 2016;Dal Cin et al, 2009;van Oosten, Peter, & Vandenbosch, 2017;.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%
“…At the same time, today, particularly in students, adverse effects are becoming greater. Social media's dark side involves decreasing academic achievement [4,5], increasing anxiety [6], cyberbullying [7,8], addictive behaviour [9], deprivation of sleep [10], sexting [11] and much more, which are major concerns. It is obvious that Social Medias are designed to be addictive as much as possible for financial gain.…”
Section: Introductionmentioning
confidence: 99%